2021
DOI: 10.1038/s42003-021-02205-y
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of complex formation between mitochondrial anion channel VDAC1 and Hexokinase-II

Abstract: Complex formation between hexokinase-II (HKII) and the mitochondrial VDAC1 is crucial to cell growth and survival. We hypothesize that HKII first inserts into the outer membrane of mitochondria (OMM) and then interacts with VDAC1 on the cytosolic leaflet of OMM to form a binary complex. To systematically investigate this process, we devised a hybrid approach. First, we describe membrane binding of HKII with molecular dynamics (MD) simulations employing a membrane mimetic model with enhanced lipid diffusion cap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 95 publications
(130 reference statements)
3
21
0
Order By: Relevance
“…Recent studies have demonstrated that some tumor-related signaling pathways alter the phosphorylation level of VDAC1, leading to cell metabolism rearrangement and affecting apoptosis and cell cycle regulation [ 38 , 39 ]. Our results showed VDAC1 protein expression and phosphorylation level at the S104 were elevated in breast cancer, colon cancer, lung adenocarcinoma, ovarian cancer, and uterine corpus endometrial carcinoma except for clear cell renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that some tumor-related signaling pathways alter the phosphorylation level of VDAC1, leading to cell metabolism rearrangement and affecting apoptosis and cell cycle regulation [ 38 , 39 ]. Our results showed VDAC1 protein expression and phosphorylation level at the S104 were elevated in breast cancer, colon cancer, lung adenocarcinoma, ovarian cancer, and uterine corpus endometrial carcinoma except for clear cell renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, VDAC1 binding would just act as an OOM anchoring/docking protein. Noteworthy, very recent data from the literature ( Haloi et al, 2021 ) suggest that VDAC1/Hexokinase-II binding promotes HK-II anchorage to the OOM, and more interestingly that this binary complex formation decreases VDAC1 conductance. In other words, favoring glycolysis decreases VDAC1 opening range, which might be in accordance with our working model suggesting VDAC1 as a part of LCFA mitochondrial uptake.…”
Section: Discussionmentioning
confidence: 99%
“…The structural basis of complex formation between VDAC and hexokinases is yet to be elucidated. It has been suggested that hexokinase first inserts into the OMM and then interacts with VDAC on the outer leaflet of OMM [92]. Complex formation between both proteins seems to be mediated by their N-terminal domains [93,94].…”
Section: Hexokinases: At the Crossroads Between Glucose Metabolism An...mentioning
confidence: 99%
“…Thus, hexokinase-dependent VDAC closure has been speculated to be an anti-apoptotic event by preventing cyt c release [95]. These discrepancies may be explained by the assumption that VDACs, besides an open and closed state, can adopt a partially closed conformation through their interaction with hexokinases [92]. This conformation would still allow some flux of low molecular weight substances while preventing the release of apoptotic factors.…”
Section: Hexokinases: At the Crossroads Between Glucose Metabolism An...mentioning
confidence: 99%